EFEKTIVITAS PEMUNGUTAN PAJAK KENDARAAN BERMOTOR DAN BEA BALIK NAMA KENDARAAN BERMOTOR DI BP2RD PROVINSI SULAWESI UTARA - Yuli ., Erithrina; Leonardus Ricky Rengkung; Charles R. Ngangi (AGRI-SOSIOEKONOMI, 2018)
This study aims to see the effectiveness and performance of Motor Vehicle Taxation (PKB) and Motor Vehicle Tranfer of Ownership Fee (BBNKB) in BP2RD North Sulawesi Province. The study was conducted at Samsat Office of North Sulawesi Province. The study period lasted from October 2017 to March 2018. This research used qualitative method through primary data and secondary data. Sampling is done used purposive sampling method. Data collection was done by observation, interview, and documentation study. The data obtained were analyzed using descriptive analysis. The result of the research shows that (1) the effectiveness of motor vehicle taxation and motor vehicle refund in BP2RD North Sulawesi Province is very effective so as to increase Pendapatan Asli Daerah (PAD) of North Sulawesi Province. This can be seen from the calculation of each type of provincial tax with an average percentage above 100%. (2) The performance of motor vehicle taxes and the transfer of motor vehicle name at the Regional Tax and Retribution Board (BP2RD) of North Sulawesi Province, shows very well as the realization exceed the specified target.